From "Sharing" to "Market Share": Sketching the Framework of the "Sharing Economy" - Heiling, Michael; Schumich, Simon (Momentum Quarterly, 2018)
"Sharing Economy" is often used to promote more social responsibility as well as conserving resources. Nevertheless, the term is also used for increasing commercial uses as well as a diverse range of uprising for-profit online-platforms. Conceptions such as “pseudo-sharing” or “share-washing” are being discussed for the market-oriented type of this phenomenon. Be that as it may, many platforms don’t conduct in the sense of “real sharing”, i.e., not making resources available without monetary compensation. This article aims to examine the structure of organizations participating in the “Sharing Economy” in Austria. The results show a diversified picture due to various forms of governance and aims of the platforms. In the range of service platforms, which focus on the allocation of human labour, we identify a strong tendency towards profit-oriented platforms. We suggest that this field should be given special attention.
Keywords: Sharing Economy; Digitalization; Platform Economy